Seroepidemiology of SARS‐CoV‐2 in pediatric population during a 16‐month period prior to vaccination. Issue 5 (31st January 2022) - Filippatos, Filippos; Tatsi, Elizabeth‐Barbara; Dellis, Charilaos; Efthymiou, Vasiliki; Margeli, Alexandra; Papassotiriou, Ioannis; Syriopoulou, Vasiliki; Michos, Athanasios
Abstract: Limited prospective serosurveillance data in children regarding severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection have been reported. We prospectively investigated SARS‐CoV‐2 seropositivity in children during a 16‐month period of the coronavirus disease 2019 (COVID‐19) pandemic, including the four waves of the pandemic, before SARS‐CoV‐2 adolescents' vaccination. Serum samples from children admitted to the major tertiary Greek pediatric hospital for any cause, except for COVID‐19 infection, were randomly collected from 05/2020 to 08/2021. The study period was divided into four 4‐month periods representing relevant epidemic waves. Total SARS‐CoV‐2 antibodies for nucleocapsid protein were determined using the Elecsys® Anti‐SARS‐CoV‐2 reagent. A total of 3099 children (0–16 years) were included in the study. A total of 344 (11.1%) seropositive children were detected (males: 205 [59.5%]; median age [interquartile range [IQR]]: 3 years [0.6–10]). Seropositivity rates (%) increased during the four 4‐month periods: 1.4%, 8.6%, 17.2%, and 17.6%, respectively. A correlation of seropositivity rates in children with new diagnosed SARS‐CoV‐2 cases in the community was detected. No significant differences were detected between males and females. Seropositivity was significantly higher in hospitalized than in nonhospitalized children and in non‐Greek compared to Greek children ( p < 0.001). The lowest seropositivity rate before school opening (9/2021) was detected in the age groups 6–12 years (14.4%) and 12–16 years (16.1%). However, compared with the other age groups, the lowest median antibody titers were observed in children 0–1 year (median [IQR]: 13.9 cut‐off index: [4.5–53.9] [ p < 0.001]). Although the seropositivity of children was related to the community epidemic waves, the exposure was limited. Low seropositivity rates in school‐age children support the need for SARS‐CoV‐2 immunization. Highlights: SARS‐CoV‐2 seropositivity rates (%) in children residing in Athens increased from 05/2020 to 08/2021 during the four 4‐month pandemic waves: 1.4%, 8.6%, 17.2%, and 17.6%, respectively. A correlation of seropositivity rates in children with new diagnosed SARS‐CoV‐2 cases in the community was detected. The lowest seropositivity rate before school opening (9/2021) was detected in the age groups 6–12 years (14.4%) and 12–16 years (16.1%). Limited exposure and low seropositivity rates in school‐age children support the need for SARS‐CoV‐2 immunization.